2021
DOI: 10.3390/w13121713
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress on Marine Microplastics Pollution Research: A Review on Pollution Occurrence, Detection, and Environmental Effects

Abstract: Recently, microplastics pollution has attracted much attention in the environmental field, as researchers have found traces of microplastics in both marine and terrestrial ecological environments. Here, we reviewed and discussed the current progress on microplastics pollution in the marine environment from three main aspects including their identification and qualification methods, source and distribution, and fate and toxicity in a marine ecosystem. Microplastics in the marine environment originate from a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 206 publications
(313 reference statements)
0
9
0
Order By: Relevance
“…Based on the overview of models and techniques, Table 2, it can be concluded that MP pollution in the marine environment can be reviewed and discussed in a wide geographical coverage worldwide in alignment with the key aspects of identification and qualification methods, source and distribution, sampling at natural sites, such as wetlands, and catchments supporting high industrial land use or close to residential densities [59], all contributing to species toxicity in their marine ecosystems [2,5,12,29,47]. Notation: Data have been presented in alphabetical order of the "Sampling sites at freshwater, coastal, urban environments" entries, following firstly the wider "geographical" naming and, secondly, the aquatic/aquifer "siting" naming.…”
Section: Modeling Of Microplastics-analytical Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the overview of models and techniques, Table 2, it can be concluded that MP pollution in the marine environment can be reviewed and discussed in a wide geographical coverage worldwide in alignment with the key aspects of identification and qualification methods, source and distribution, sampling at natural sites, such as wetlands, and catchments supporting high industrial land use or close to residential densities [59], all contributing to species toxicity in their marine ecosystems [2,5,12,29,47]. Notation: Data have been presented in alphabetical order of the "Sampling sites at freshwater, coastal, urban environments" entries, following firstly the wider "geographical" naming and, secondly, the aquatic/aquifer "siting" naming.…”
Section: Modeling Of Microplastics-analytical Techniquesmentioning
confidence: 99%
“…Global environmental alarm and social sensitivity revealed that microplastics (MPs) are the most notable type of plastic degradation and pollution that has attracted much attention among researchers, who have detected MP traces in marine and terrestrial environments [5][6][7]. Plastic debris are recognized as threatening indicators against natural environment and wildlife habitats by human activity.…”
Section: Introduction 1plastics In a Global Environmental Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the commonly used filling particles mainly include rubber particles SBR, EPDM, TPE, etc., and the particle size is usually between 0.5 and 2.5 mm. All of these can be categorized as micro-plastic particles, and they will be continuously lost in the process of use, and they will need to be continuously supplemented (Liu et al 2021). The particles that are lost can be carried by drainage systems into oceans, causing micro-plastic pollution (Rezania et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, MPs pose a potential threat to the environment , and they can enter the marine ecosystem directly or indirectly . Synthetic bers, tires, and city dust are the principal sources of MPs in the ocean (Liu et al 2021). Neto et al (2020) tested 965 sh samples from the southeastern and southern coasts of Brazil, and we found that all contained plastics in their bodies.…”
Section: Introductionmentioning
confidence: 99%